The effects of additional niacin during gestation and lactation on sow and litter performance - Thaler, R.C.; Turlington, L.M.; Allee, G.L.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixty first-litter sows were utilized to evaluate the effects of additional niacin on sow and litter performance through two parities. The control diet provided sows with 50 mg niacin daily during gestation and 100 mg niacin daily during lactation. Dietary treatments were formulated to provide sows with either 5 or 10 times the level of supplemental niacin in the control diet. Litter size was equalized within dietary treatment by 24 hr after farrowing. During the first parity, sows fed additional niacin tended to have fewer total pigs born and pigs born alive (linear effect of niacin P<.10). In addition, sows fed additional niacin had fewer pigs equalized/litter (linear P(.05 and quadratic P<.06 effect of niacin), but tended to wean more pigs/litter and had a 6% greater pig survival rate than those fed the control diet. Average pig birth wt increased linearly (P<.05) as level of added niacin increased. Also, average pig wt and Litter wt at weaning were numerically higher for sows fed additional niacin during lactation. Sows fed the 250/500 mg/d niacin gestation-lactation sequence had more backfat on d 108 of gestation (quadratic effect of niacin, P<.05), but also lost more backfat during lactation (quadratic effect of niacin, P<.05).
Keywords: Swine; Niacin; Gestation; Lactation; Performance